From Islamic School to Global Stage: Islamic Education Strategies in Building Internationally Standardized English Language Competencies - Naily Inayatul Maghfirah; Irfan Masrur (Universitas Maritim Raja Ali Haji (UMRAH), 2026)
This article aims to examine Islamic education strategies in developing internationally recognized English language competencies for Islamic students. The globalization of Islamic educational institutions is transforming from local educational institutions into actors capable of competing on the global stage. One of the main challenges in this process is mastering English as an international language without neglecting Islamic values. This research uses a qualitative approach with literature study methods and conceptual analysis of educational policies, curricula, and English language learning practices in Islamic educational institutions. The results of the study indicate that the integration of Islamic values ​​in English learning, the implementation of a global competency based curriculum, improving teacher quality through professional training, and the use of digital technology are key strategies in improving students' English language skills. In addition, a supportive learning environment, international collaboration, and a communicative approach based on an Islamic context have been proven to strengthen students' motivation and confidence in using English actively. This article concludes that Islamic education has great potential to produce of Muslims generation who not only excel in internationally recognized English language proficiency but also have Islamic character and global competitiveness. These findings are expected to serve as a reference for policy makers and practitioners of Islamic education in designing adaptive and sustainable English language learning.